(Short Communication) Study of the Hatchery of Tiger Grouper (Epinephelus fuscoguttatus) Household Scale in Penyabangan Village, Gerokgak District, Buleleng Regency, Bali Province - Muh Sulaiman Dadiono; Liga Insani (Journal of Aquaculture Science, 2020)
Hatchery of tiger grouper (Epinephelus fuscogutattus) household scale is one of the contributors to the increase in national grouper seed production. with the hatchery of household-scale grouper, the demand for grouper seed can be fulfilled as well as improving the community's economy. This study aims to determine the hatchery of household-scale tiger grouper which includes the provision of feed, hatching eggs, water quality management, harvesting, Hatching Rate (HR) and Survival Rate (SR). Data collection methods by interview, observation and active participation. Observation results related to seeding began with the provision of natural food to harvest the seeds measuring 2.7-3 cm. Hatching Rate (HR) reaches 80% and Survival Rate (SR) reaches 20%. The seeds produced were 120,000 per cycle. Seed yields are 24,000 per cycle. Keyword : Hatchery, Tiger Grouper, Epinephelus fuscogutattus, Household Scale